The Book “Bughyat al-Talab fi Tarikh Halab” by Ibn al-Adim as a Source for Kurdish History: A Historical Analytical Study - Dilman Yousif Ahmed; Falah Khairi Mirzo (Zanco Journal of Human Sciences, 2025)
This research examines the book “Bughyat al-Talab fi Tarikh Halab” by Ibn al-Adim as a Source for Kurdish History through an analytical historical study. The book is considered an encyclopedic reference for the history of Aleppo and contains valuable information highlighting the role of Kurdish figures, particularly in the political, military, literary, and religious spheres. The study focuses on the period when kings and princes of the Ayyubid dynasty-controlled Aleppo specifically and the Levant in general, during which Kurds were given opportunities to play significant roles. This research sheds light on the Kurdish figures mentioned in the book. Ibn al-Adim relied on his personal observations and close relationships with his friends and acquaintances. As a historian and writer, he maintained connections with many prominent figures in politics, the military, and literature. His extensive travels to various cities enriched his knowledge, which was reflected in his historical writings. His work became a crucial source for later historians who relied on his writings as a primary reference for studying that era.